2013
DOI: 10.1161/strokeaha.113.003226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MLC601 on Early Vascular Events in Patients After Stroke

Abstract: Background and Purpose-Early vascular events are an important cause of morbidity and mortality in the first 3 months after a stroke. We aimed to investigate the effects of MLC601 on the occurrence of early vascular events within 3 months of stroke onset. Methods-Post hoc analysis was performed on data from subjects included in the CHInese Medicine Neuroaid Efficacy on Stroke recovery (CHIMES) study, a randomized, placebo-controlled, double-blinded trial that compared MLC601 with placebo in 1099 subjects with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
(19 reference statements)
4
22
0
Order By: Relevance
“…We have also previously shown a reduction in early vascular events with MLC601 treatment for 3 months [19]. In CHIMES-E, we noted consistently favorable treatment effect for all assessment time points but the largest effect was seen at 6 months with a gradual decline at 24 months; however, no difference in rates of vascular events was observed.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We have also previously shown a reduction in early vascular events with MLC601 treatment for 3 months [19]. In CHIMES-E, we noted consistently favorable treatment effect for all assessment time points but the largest effect was seen at 6 months with a gradual decline at 24 months; however, no difference in rates of vascular events was observed.…”
Section: Discussionsupporting
confidence: 71%
“…We have previously demonstrated that post-stroke use of concomitant secondary prevention treatments and rehabilitation in CHIMES were high and similar between the two treatment groups [19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies to assess the benefit and safety of MLC601 in stroke patients using different clinical outcome have been performed [10][11][12][13][14][15][16][17][18] . The Chinese Medicine Neuroaid Efficacy on Stroke recovery (CHIMES) trial, which compared MLC601 with placebo in 1,099 patients with acute ischemic stroke of intermediate severity, reported a reduction in early recurrent vascular events and vascular deaths in post-stroke patients [11,19,20] . Interestingly, in the Philippine cohort of the CHIMES trial, which included more patients with predictors of poorer prognosis, functional and neurological outcomes were improved in favor of MLC601 [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The updated meta-analysis showed a pooled odds ratio in favor of NeuroAiD [27]. Furthermore, treatment with NeuroAiD was associated with a reduction in risk of early vascular events after a stroke [30]. More recently, the extension study of this randomized, placebo-controlled, double blind trial has provided evidence of its benefit on long-term functional outcome persisting over time up to 18 months after a stroke with an excellent safety profile [31].…”
Section: Introductionmentioning
confidence: 99%